Characterization of Vibrio metschnikovii and Vibrio gazogenes by DNA-DNA hybridization and phenotype. - Farmer, J J (1988)
Vibrio metschnikovii and Vibrio gazogenes are two new Vibrio species that have been little studied. Thirteen strains of V. metschnikovii were highly related to the type strain, NCTC 8443, by DNA-DNA hybridization. Relatedness values were 83 to 90% at 60 degrees C and 75 to 84% at the more stringent 75 degrees C. Divergence values ranged from 0.7 to 1.9. Strains of V. metschnikovii were oxidase negative and did not reduce nitrate to nitrite. The other phenotypic characteristics agreed with published data. Twenty-three strains of V. gazogenes were isolated from salt marshes and marshy areas on the coast of North and South Carolina. A new medium, marine agar supplemented with an additional 2.5% agar, reduced the problem of swarming by marine Vibrio species and enhanced the isolation of V. gazogenes and other organisms. By DNA-DNA hybridization, 22 of 23 strains were 76% or more related to the type strain of V. gazogenes, ATCC 29988. However, four DNA hybridization subgroups were defined on the basis of divergence values and/or phenotype. Strains of DNA group 1 were more highly related to each other, and this group contained the type strain and six other strains. Strains of DNA group 2 were more highly related to each other, and this group contained reference strain ATCC 43942 and 14 other strains. Strains of DNA group 1 did not ferment melibiose or D-sorbitol (one strain was sorbitol positive), but strains of DNA group 2 fermented both sugars. A revised phenotypic description of V. gazogenes based on 24 strains was written on the basis of reactions (within 2 days of incubation) at 25 degrees C in media supplemented with Na+, K+, and Mg2+. Positive results (100% positive unless indicated) included motility; gas production during fermentation (96% at 2 days, 100% at 3 to 7 days); growth in nutrient broth with the addition of 1% NaCl (88%), 2% NaCl, 3.5% NaCl, 6% NaCl, 8% NaCl, and 10% NaCl (92%); dry red or orange colonies on marine agar; and fermentation of L-arabinose, cellobiose, D-galactose (88%), D-glucose, lactose (88%), maltose, D-mannitol (96%), D-mannose, salicin, sucrose, trehalose, and D-xylose. Negative results included oxidase; nitrate reduction to nitrite (4% positive); indole production; lysine decarboxylase; ornithine decarboxylase; arginine dihydrolase; swarming; growth on TCBS agar; growth in nutrient broth with 0% NaCl, 0.1% NaCl, 0.2% NaCl, 0.3% NaCl, and 0.4% NaCl (8% positive); and fermentation of adonitol, D-arabitol, dulcitol, erythritol, D-galacturonate, i-inositol, alpha-methyl-D-glucoside, raffinose, and L-rhamnose. Variable results were found for the Voges-Proskauer reaction (62% positive), growth in nutrient broth plus 0.5% NaCl (29%) and 12% NaCL (42%), and fermentation of melibiose (71%) and D-sorbitol (71%).